The Potential of Local Ginger as Antioxidant on Full Fat Mayonnaise (Faculty of Animal Science Universitas Brawijaya, 2019)
The aims of this study were to investigate the potential of local ginger for natural antioxidants on full-fat mayonnaise. The used materials were sunflower oil, vinegar, egg yolk, white pepper, salt, sugar, mustard, and local ginger extract. The study was done by using laboratory experimental with Nested Completely Randomized Design with 2 factors and 3 replications. The first factor was used three ginger varieties, namely elephant ginger/(Zingiber officinale var. Roscoe) (G), red ginger (M)/(Zingiber officinale var. Rubrum) and emprit ginger (E)/(Zingiber officinale var. Amarum). The second factor was the addition levels, which were 0.5% (a), 1% (b) and 1.5% (c). The observed variables include pH, viscosity, moisture content and antioxidant activity (IC50). Data were analyzed by using analysis of variance. The result showed that the used different ginger material and different levels of addition did not give significant effect (P>0.05) on pH analysis and gave highly significant effect (P<0.01) of the antioxidant activity, viscosity and moisture content. The study could conclude that mayonnaise added with red ginger showed physicochemical properties better than added with emprit ginger and gajah ginger. In addition, the best result was found in 1.5% ginger addition of each ginger variety in terms of physicochemical qualities of the mayonnaise.